1993
DOI: 10.2307/1591674
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Detection Limit of the Polymerase Chain Reaction for Chicken Infectious Anemia Virus

Abstract: Chicken infectious anemia virus (CIAV) DNA in infected cell cultures and chicken tissues was detected using a polymerase chain reaction (PCR) assay. The complete CIAV genome of several strains was amplified in two segments with two sets of primer pairs. The DNA segments of four CIAV strains and full-length Cux-1 strain DNA were cloned. After amplification, 100 original genome equivalents were detected by Southern hybridization. The sensitivity of the assay was enhanced considerably by performing a reamplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…10,20,22,24 Although the use of nested PCR showed improved detection sensitivity by 10-100-fold, 10,20 it increases the cost and time required for vaccine evaluation with no extra positive impact on the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…10,20,22,24 Although the use of nested PCR showed improved detection sensitivity by 10-100-fold, 10,20 it increases the cost and time required for vaccine evaluation with no extra positive impact on the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Another PCR (Noteborn et al, 1992a,b) and a nested-PCR (Soiné et al, 1993) were also reported only for the detection of CAV in MSB-1 cell cultures infected with CAV rather than directly in chicken tissues from field cases suspected of CAV, and had already indicated as well that the PCR assay is highly sensitive for the diagnosis of CAV. The sensitivity of the nested-PCR from Soiné et al (1993) was evaluated in regard to the amplification of cloned CAV DNA and could detect as little as one calculated virus genome equivalent, suggesting that the nested-PCR is an even more sensitive and thus more suitable test for CAV diagnosis than PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Another PCR (Noteborn et al, 1992a,b) and a nested-PCR (Soiné et al, 1993) were also reported only for the detection of CAV in MSB-1 cell cultures infected with CAV rather than directly in chicken tissues from field cases suspected of CAV, and had already indicated as well that the PCR assay is highly sensitive for the diagnosis of CAV. The sensitivity of the nested-PCR from Soiné et al (1993) was evaluated in regard to the amplification of cloned CAV DNA and could detect as little as one calculated virus genome equivalent, suggesting that the nested-PCR is an even more sensitive and thus more suitable test for CAV diagnosis than PCR. However, due to its sensitivity, the authors indicate that the nested-PCR is much more prone to cross contamination and therefore requires extreme caution in handling field samples and has to be carried preferably in separate facilities and equipment (Soiné et al, 1993), a matter that has to be even better observed when a nested-PCR is considered for routine use in diagnostic laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Two oligonucleotide primers flanking fragment A were as follows. Forward primer (CAV5): 5  -ATC GAA TTC CGA GTG GTT ACT ATT CC -3  (nt 2317-23) and the reverse primer (CAV6): 5  -GAA GGA TCC CTC ATT CTT AGT GGC -3  (nt 1515-1492) (Soiné et al, 1993).…”
Section: Amplification Of Dna Fragments By Polymerase Chain Reaction mentioning
confidence: 99%